2015
DOI: 10.1038/srep14567
|View full text |Cite|
|
Sign up to set email alerts
|

Rumen microbial community composition varies with diet and host, but a core microbiome is found across a wide geographical range

Abstract: Ruminant livestock are important sources of human food and global greenhouse gas emissions. Feed degradation and methane formation by ruminants rely on metabolic interactions between rumen microbes and affect ruminant productivity. Rumen and camelid foregut microbial community composition was determined in 742 samples from 32 animal species and 35 countries, to estimate if this was influenced by diet, host species, or geography. Similar bacteria and archaea dominated in nearly all samples, while protozoal comm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

164
1,233
10
46

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 1,200 publications
(1,525 citation statements)
references
References 52 publications
164
1,233
10
46
Order By: Relevance
“…Although rumen microbial community composition varies with diet and host, a 'core microbiome' is found across a wide geographical range [25,31,58]. Ruminants depend on these rumen microorganisms to digest nutritional components in feedstuffs and to convert them into proteins, carbohydrates, VFAs and gases [52].…”
Section: Core Prokaryotic Communities In the Rumenmentioning
confidence: 99%
See 1 more Smart Citation
“…Although rumen microbial community composition varies with diet and host, a 'core microbiome' is found across a wide geographical range [25,31,58]. Ruminants depend on these rumen microorganisms to digest nutritional components in feedstuffs and to convert them into proteins, carbohydrates, VFAs and gases [52].…”
Section: Core Prokaryotic Communities In the Rumenmentioning
confidence: 99%
“…Jami et al [30] found that Bacteroidetes was more abundant than Firmicutes in older bovines that had a diet composed mainly of plant fiber, but they were less abundant in newborns. The dominance of Bacteroidetes or Firmicutes could be attributable to the variations in diet, climate, and farming practices in a wide geographical range [2,25]. However, in a narrow geographical range, diet composition and host species had little impact on the dominant position of these two phyla [3,11,83].…”
Section: Core Prokaryotic Communities In the Rumenmentioning
confidence: 99%
“…A recent publication (Henderson et al, 2015) reported that rumen microbial community composition varies with diet and host, but a core microbiome can be found across a wide geographical range. Thus, ruminal yeast could be influenced by both diet and host.…”
Section: Resultsmentioning
confidence: 99%
“…According to Lund's (1974) hypothesis, yeast could be introduced to the rumen from feed and water, more recently, Henderson et al (2015) studied the microbial community composition of the ruminant and proposed that rumen microbes' differences are attributed to diet. This assumption can be important for future studies on rumen microbiology and consider the analysis of yeast profile in diets and feedstuffs to confirm this hypothesis.…”
Section: Resultsmentioning
confidence: 99%
“…5B). Based on the reduced number of Methanomassiliicoccaceae, which was found mainly in the rumen (Henderson et al, 2016) and anaerobic digester (Gonzalez-Martinez et al, 2016), and obviously increased methane flux after addition of NH 4 NO 3 (Fig 3A, and B), it suggested that this kind of archaea may be not the key biogenic source for methane production. RDA analysis showed that ammonium nitrogen and Methanosarcinaceae were positive.…”
Section: Discussionmentioning
confidence: 99%